Tailoring the magnetic anisotropy of cobalt-gold thin films - DEĞER, CANER (SCIENTIFIC TECHNICAL RESEARCH COUNCIL TURKEY-TUBITAK, 2018)
Magnetic cobalt-gold thin films (Co Au(1_)) are grown on silicon (100) surfaces by using a sputter deposition technique. Magnetic anisotropy of the films is investigated by ferromagnetic resonance (FMR). Magnetic properties are explored by micromagnetic simulations based on the metropolis algorithm. Effective magnetic anisotropy is gradually increased with Co concentration. In-plane axial anisotropy exists for all samples and it is enhanced with a Co concentration of similar to 40% corresponding optimal cluster size, and intercluster separation. Segregation and coalescence of Co clusters caused by different Co concentrations strongly affect magnetic properties of the thin films. Therefore, the study revealed that magnetic behavior of Co Au(1-x) thin films can be tuned by changing Co concentration.
Keywords: Magnetosputtering; magnetic thin films; ferromagnetic resonance; magnetic anisotropy; GIANT MAGNETORESISTANCE; CO; SUPERLATTICES; TEMPERATURE; GROWTH